Antiproliferative and Anti-Migratory Activities of an Extract from Fridericia platyphylla Leaves and Its Molecular Profile - Brito, Jhonathas Aparecido R.; de Jesus A. Miranda, Amanda; Lima, Victor Antonio S.; dos Santos S. Buna, Samuel; do Rosário, Marcelino S.; Lima, Rafael F.; Martins, Monique M.; de Andrade, Marcelo S.; Nascimento, Maria D. S. B.; da Silva Bolzani, Vanderlan [UNESP]; de Azevedo-Santos, Ana Paula Silva; Lima, Josélia Alencar; et al. (MDPI, 2025)
Fridericia platyphylla, a member of the Bignoniaceae family, is widely recognized as a rich source of flavonoids with significant biopharmacological potential. This study aimed to perform a chemical annotation of its metabolites and to evaluate the antitumor activity of the hydroalcoholic extract from its leaves. The chemical diversity of this specimen was analyzed using liquid chromatography coupled with tandem mass spectrometry and Molecular Networking. Fifteen significant phenolic compounds were annotated, including phenolic acid derivatives, flavonoid glycosides, and flavone aglycones. Furthermore, the antiproliferative activities against human cervical cell lines, adenocarcinoma HPV 18 positive (HeLa) and carcinoma HPV 16 positive (SiHa), in vitro, exhibited distinct inhibitory effects, with IC50 values of 44.78 and 66.97 µg mL-1, respectively. The extract inhibited cell migration and exhibited cytotoxic effects by reducing the viability of HeLa and SiHa cells, suggesting its potential as a therapeutic candidate for cervical cancer. Therefore, given the significant antiproliferative and anti-migratory activity, these results open up prospects for investigating F. platyphylla leaf extract in the development of alternative therapies for cervical cancer.